Comprehensive policy for the criminal protection of intellectual property on the Internet (2013)
The new telecommunications technologies under the principles of the information society, have led us to a digital age that demands answers to the new challenges in all normative orders, and neither criminal dogmatic nor criminal policy are unrelated to th